A ESCOLHA PROFISSIONAL NO ENEM: entre o ideal e as imposições do real - Halabe, Dannilo Jorge Escorcio (2012)
Study to be conducted about the choice of profession in the National Secondary Education Examination (ENEM), a methodology that replaces the traditional examination of Federal Universities in Brazil since 2009. Analyzes the motivations of young people entering the Faculty of Education, Federal University of Maranhão (UFMA). Aims to analyze the adequacy of life projects for students and the real opportunity to enter in UFMA and conflicts that may arise from this choice. In accordance with the historical-dialectical methodology, the study starts by analyzing the economic and social transformations due to the restructuring process of the 1970s. Examines the consequences of these changes in Brazilian educational legislation to create the ENEM, as a methodology for evaluating the high school, and its reformulation to serve as National Exam for entry to the Brazilian Federal Universities. This relates to the adequacy of the capitalist system as a strategy to reproduce the antagonism between classes. Investigates the relationship of the youth interviewed with their families and schools, analyzing the pressures they exert at the time of selection. Highlights finally, the impressions of the subject and the role in choosing your professional future ahead the National Examination of Secondary Education.